2018
DOI: 10.1128/aac.01647-17
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Relationship between Vancomycin Trough Concentration and 24-Hour Area under the Concentration-Time Curve in Neonates

Abstract: Bacterial sepsis is a major cause of morbidity and mortality in neonates, especially those involving methicillin-resistant (MRSA). Guidelines by the Infectious Diseases Society of America recommend the vancomycin 24-h area under the concentration-time curve to MIC ratio (AUC/MIC) of >400 as the best predictor of successful treatment against MRSA infections when the MIC is ≤1 mg/liter. The relationship between steady-state vancomycin trough concentrations and AUC values (mg·h/liter) has not been studied in an A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
18
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 37 publications
4
18
2
Order By: Relevance
“…The clearance and volume estimates determined in our study are similar to those previously published in neonatal populations, suggesting that these findings have the potential to be extended to other institutions. 11,20,22 There are few studies that have published the effects of implementing a new vancomycin dosing guideline in a NICU. 23,24 A study by Grimsley and colleagues sought to evaluate population pharmacokinetics of vancomycin in neonates due to the high percentage, approximately 30% of vancomycin troughs being <5 mg/L and only 33% of first troughs in their target range of 5 to 12 mg/L.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The clearance and volume estimates determined in our study are similar to those previously published in neonatal populations, suggesting that these findings have the potential to be extended to other institutions. 11,20,22 There are few studies that have published the effects of implementing a new vancomycin dosing guideline in a NICU. 23,24 A study by Grimsley and colleagues sought to evaluate population pharmacokinetics of vancomycin in neonates due to the high percentage, approximately 30% of vancomycin troughs being <5 mg/L and only 33% of first troughs in their target range of 5 to 12 mg/L.…”
Section: Discussionmentioning
confidence: 99%
“…7 Current data from NICU studies suggest a minimum vancomycin total daily dose of 40 to 60 mg/kg/day [8][9][10] to achieve desired pharmacodynamic endpoints when the MIC is ࣙ1 in some age groups, but there are still very limited data correlating vancomycin efficacy with trough concentrations or AUC-to-MIC ratios in pediatric or neonatal patients. 7,11 Over the past decade, research conducted to study vancomycin PK patterns in neonates has demonstrated that size, renal function, and age are predictors of vancomycin clearance. [7][8][9][10][11][12][13][14][15][16] Current clinical practice extrapolates neonatal vancomycin dosing and target trough concentrations from adult data.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Because the kidneys play an important role in drug metabolism and excretory, and it is the target organ by PU-48 diuretic role. Therefore, understanding the pharmacokinetic and pharmacodynamic (PK-PD) relationship of PU-48, and its underlining mechanism, is critical [ 49 , 50 , 51 , 52 ]. In the present research, low recoveries of PU-48 parent drug indicated that PU-48 had an almost complete metabolism in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence supports the efficacy of TDM based on the area under the concentration-time curve for 24 hours (AUC 24 ). [19][20][21] However, a more practical way of vancomycin TDM especially in pediatric care is still using trough levels because multiple blood samples per patient are required for monitoring AUC 24 . 22 Therefore, this study was designed to evaluate the therapeutic outcomes and resistance development risks along with potential renal toxicities of vancomycin therapy depending on initial steady-state trough levels among pediatric patients with GPB infections.…”
Section: Introductionmentioning
confidence: 99%